THE ANALYSIS OF INCOMPLETENESS FILLING OF INPATIENT MEDICAL RECORDS AT ISLAMIC HOSPITAL (RSI) PEMBINA KESEJAHTERAAN UMMAT (PKU) MUHAMMADIYAH OF NORTH MALUKU IN 2016 - Maya Sari Soamole (UHAMKA Press, 2019)
The incomplete filling of medical record documents can cause various problems in the quality of service to the patients. The document of medical record is important to produce accurate and continuous information of patient care. The purpose of this study is to analyze the possible causes of incomplete filling of medical records for inpatients at Islamic Hospital PKU Muhammadiyah of North Maluku in 2016.This research was a qualitative research using documentation study, observation and in-depth interviews. Informants were determined by purposive sampling method. The number of informants was 13 people (medical record officer, registration officer, midwives, nurses, BPJS officer, pharmacy officer, nutrition officer, general practitioners, medical specialists). A simple quantitative research was done descriptively to see the incompleteness contents of medical records of all inpatients in January 2016 amounted to 127 medical record files.This study concluded that all medical records in January 2016 were incomplete. The medical records were categorized incomplete if one or more data were not filled or unclearly written. The most incomplete medical records occurred in the following areas: the patient's social data on (70.47%) the graph sheets, clinical data on nutritional form (98.74%), the recording of name, signature, date of nutritional data entry (63.25%), and 63 medical records were corrected inappropriately. The interviews showed that incompleteness were due to lack of human resources capability, inadequate medical records facilities, rules and regulation, and inadequate medical record information system. The human resources related to incompetent medical personnel and lack of clinical staff knowledge on medical record requirements.The results of the study recommended that the hospital management was to increase the number of qualified medical record staff, developed rules and regulations, improved medical record facilities, trained clinical personnel on the filling of medical records and enforced then to do so.